Uji Multilokasi Sepuluh Galur Padi Untuk Menghasilkan Varietas Unggul Baru - Jaenudin Kartahadimaja; Eka Erlinda Syuriani (Politeknik Negeri Lampung., 2018)
Reduced productive rice fields to non-paddy fields, most possible extension of the nationalrice cultivation area to the suboptimal lands reaching Â± 91.9 million ha. Technologypackages that can be applied include the use of new improved rice varieties through theassembling of varieties that have high yield potential, resistant to suboptimal soil stress. Theobjective of the research is to produce new superior rice varieties that are available invarious environments. The study used a split-plot design, as the main plot is an environmentconsisting of rice paddies and gogo, as a subplot is the genotype of rice. The treatment ineach environment is prepared using the Randomized Complete Block Design (RCBD). Thetreatment consisted of 10 new rice strains and four varieties as a comparison. Variablesobserved (1) plant height; (2) the maximum number of shoots; (3) number of productiveshoots; (4) long panicle; (5) the number of grains per panicle; (6) the amount of graincontent of each panicle; (7) the number of empty grains per panicle; (8) weight of 1000grains of grain; (9) grain yield of each clump; (10) grain yield per hectare. Data wereanalyzed by variance if there was a difference between mean, median treatment, followed byLsd test at 5% level. The adaptability and yield stability of each strain was determined basedon the value of the coefficient of diversity (KK) (Francis and Kenneberg, 1978) in Syukur etal., (2012). The results showed that seven new rice strains had adaptations both planted asupland rice and lowland rice, namely strains B3, B4, F2, F3, H1, H4, and L2.